Menstrual cycle influence on cognitive function and emotion processing—from a reproductive perspective - Sundström Poromaa, Inger; Gingnell, Malin (Frontiers in Neuroscience, 2014)
The menstrual cycle has attracted research interest ever since the 1930s. For many researchers the menstrual cycle is an excellent model of ovarian steroid influence on emotion, behavior, and cognition. Over the past years methodological improvements in menstrual cycle studies have been noted, and this review summarizes the findings of methodologically sound menstrual cycle studies in healthy women. Whereas the predominant hypotheses of the cognitive field state that sexually dimorphic cognitive skills that favor men are improved during menstrual cycle phases with low estrogen and that cognitive skills that favor women are improved during cycle phases with increased estrogen and/or progesterone, this review has not found sufficient evidence to support any of these hypotheses. Mental rotation has gained specific interest in this aspect, but a meta-analysis yielded a standardized mean difference in error rate of 1.61 (95% CI -0.35 – 3.57), suggesting, at present, no favor of an early follicular phase improvement in mental rotation performance. Besides the sexually dimorphic cognitive skills, studies exploring menstrual cycle effects on tasks that probe prefrontal cortex function, for instance verbal or spatial working memory, have also been reviewed. While studies thus far are few, results at hand suggest improved performance at times of high estradiol levels. Menstrual cycle studies on emotional processing, on the other hand, tap into the emotional disorders of the luteal phase, and may be of relevance for women with premenstrual disorders. Although evidence at present is limited, it is suggested that emotion recognition, consolidation of emotional memories, and fear extinction is modulated by the menstrual cycle in women. With the use of functional magnetic resonance imaging, several studies report changes in brain reactivity across the menstrual cycle, most notably increased amygdala reactivity in the luteal phase.